LncRNA SNHG16 Promotes Hepatocellular Carcinoma Proliferation, Migration and Invasion by Regulating miR-186 Expression - Chen, Hang (J Cancer, 2019)
Long non-coding RNA (lncRNA) and microRNA (miRNA) play an important role in genesis and progression of tumors. The aim of this study was to explore the expression, biological function and molecular mechanism of small nucleolar RNA host gene 16 (SNHG16) in HCC. RT-qPCR was conducted to evaluate the expression level of SNHG16 in HCC tissues and cell lines. Our findings showed for the first time that SNHG16 was up-regulated in HCC tissues and cell lines. The expression of SNHG16 in cancer tissues was highly correlated with tumor size, TNM stage, ALT expression level and HBV DNA level. Moreover, cell proliferation, migration and invasion were detected by CCK-8 assay, transwell migration assay and transwell invasion assay, respectively. Xenograft tumor experiment was used to determine the biological function of SNHG16 in vivo. As revealed by our data, SNHG16 accelerated the proliferation, migration and invasion of HCC cell. SNHG16 facilitated tumor formation in vivo. Next, the relationship between SNHG16, miR-186 and ROCK1 were analyzed using bioinformatics analysis, qRT-PCR, luciferase reporter assay and western blot. Further molecular mechanism studies reported that the expression of SNHG16 was negatively correlated with the level of miR-186 and SNHG16 directly bound to miR-186. SNHG16 and miR-186 repressed each other. Notably, rescue experiments were conducted and showed that miR-186 reversed the effect of SNHG16 on cell. Taken together, SNHG16 promoted HCC cell proliferation, migration and invasion by functioning as a competitive endogenous RNA (ceRNA) to negatively regulate miR-186 expression. Our data suggested that SNHG16 might be a potential biomarker and a new therapeutic target for HCC.